2016
DOI: 10.3390/ijms17040586
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 9p21 and ABCA1 Genetic Variants and Their Interactions on Coronary Heart Disease and Ischemic Stroke in a Chinese Han Population

Abstract: The single nucleotide polymorphisms (SNPs) related to both coronary heart disease (CHD) and ischemic stroke (IS) in Chinese individuals have not been identified definitely. This study was developed to evaluate the genetic susceptibility to CHD and IS on the chromosome 9p21 and the adenosine triphosphate (ATP)-binding cassette transporter A1 genes (ABCA1) in a Chinese Han population. Genotypes of the rs1333040, rs1333042, rs4977574, rs2066715 and rs2740483 SNPs were determined in 1134 unrelated patients (CHD, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
2
24
1
Order By: Relevance
“…The normal values of serum TC, TG, HDL-C, LDL-C, ApoA1, ApoB levels and the ApoA1/ApoB ratio in our Clinical Science Experiment Center were 3.10-5.17, 0.56-1.70, 0.91-1.81, 2.70-3.20 mmol/L; 1.00-1.78, 0.63-1.14 g/L; and 1.00-2.50; respectively (24). The individuals with TC > 5.17 mmol/L and/or TG covariance analysis (ANCOVA).…”
Section: Diagnostic Criteriamentioning
confidence: 83%
“…The normal values of serum TC, TG, HDL-C, LDL-C, ApoA1, ApoB levels and the ApoA1/ApoB ratio in our Clinical Science Experiment Center were 3.10-5.17, 0.56-1.70, 0.91-1.81, 2.70-3.20 mmol/L; 1.00-1.78, 0.63-1.14 g/L; and 1.00-2.50; respectively (24). The individuals with TC > 5.17 mmol/L and/or TG covariance analysis (ANCOVA).…”
Section: Diagnostic Criteriamentioning
confidence: 83%
“…The normal values in our Clinical Science Experiment Center were 3.10-5.17 mmol/L for TC, 0.56–1.70 mmol/L for TG, 0.91–1.81 mmol/L for HDL-C, 2.70–3.20 mmol/L for LDL-C, 1.00–1.78 g/L for ApoA1, 0.63–1.14 g/L for ApoB, and 1.00–2.50 for the ApoA1/ApoB ratio. The participants with TC > 5.17 mmol/L, and/or TG > 1.70 mmol/L were defined as hyperlipidemic [ 24 , 25 ]. Hypertension was defined as a systolic blood pressure of 140 mmHg or greater, and/or a diastolic blood pressure of 90 mmHg or higher [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from leucocytes of venous blood using the phenol-chloroform method. Genotyping of the SNPs was accomplished by the Snapshot technology platform in the Center for Human Genetics Research, Shanghai Genesky Bio-Tech Co. Ltd. [ 25 , 27 29 ]. The restriction enzymes for the loci were SAP (Promega) and Exonucleasel (Epicentre).…”
Section: Methodsmentioning
confidence: 99%
“…However, the associations between rs4977574 and the risk of CAD are likely to be varied across different ethnicities. To date, most of the studies on ANRIL rs4977574 polymorphism focused on Caucasians, [ 17 , 20 , 21 ] and few studies are available on Asians. Huang et al carried out a case-control study of 590 Chinese CAD patients and 482 non-CAD patients subjects and found that ANRIL rs4977574 polymorphism was associated with a significantly increased risk of CAD in females (χ 2 = 10.29, P = .003, OR = 2.14, 95% CI 1.31–2.77).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al carried out a case-control study of 590 Chinese CAD patients and 482 non-CAD patients subjects and found that ANRIL rs4977574 polymorphism was associated with a significantly increased risk of CAD in females (χ 2 = 10.29, P = .003, OR = 2.14, 95% CI 1.31–2.77). [ 22 ] Additional studies on Chinese, Japanese and people from other Asian countries also suggested that ANRIL rs4977574 polymorphism was associated with an increased CAD risk, [ 16 , 17 , 21 , 23 – 24 ] but hitherto, no meta-analysis of ANRIL rs4977574 polymorphism and CAD risk is available. In the present study, we carried out a meta-analysis of the overall effect of ANRIL polymorphism rs4977574 (A >G) on CAD risk in Asian subjects.…”
Section: Introductionmentioning
confidence: 99%